Evident but context‐dependent mortality of fish passing hydroelectric turbines. Issue 3 (17th January 2022) - Radinger, Johannes; van Treeck, Ruben; Wolter, Christian
Abstract: Globally, policies aiming for conservation of species, free‐flowing rivers, and promotion of hydroelectricity as renewable energy and as a means to decarbonize energy systems generate trade‐offs between protecting freshwater fauna and development of hydropower. Hydroelectric turbines put fish at risk of severe injury during passage. Therefore, comprehensive, reliable analyses of turbine‐induced fish mortality are pivotal to support an informed debate on the sustainability of hydropower (i.e., how much a society is willing to pay in terms of costs incurred on rivers and their biota). We compiled and examined a comprehensive, global data set of turbine fish‐mortality assessments involving >275, 000 individual fish of 75 species to estimate mortality across turbine types and fish species. Average fish mortality from hydroelectric turbines was 22.3% (95% CI 17.5–26.7%) when accounting for common uncertainties related to empirical estimates (e.g., handling‐ or catch‐related effects). Mortality estimates were highly variable among and within different turbine types, study methods, and taxa. Technical configurations of hydroelectric turbines that successfully reduce fish mortality and fish‐protective hydropower operation as a global standard could balance the need for renewable energy with protection of fish biodiversity. Abstract : Mortalidad evidente, pero dependiente del contexto, de peces que pasan por turbinas hidroeléctricas Resumen: Globalmente, las políticas que buscan la conservación de especies, el flujo libre de ríos y la promoción de la hidroeléctrica como una energía renovable y como un medio para reducir el carbono en sistemas de energía generan pros y contras entre la protección de la fauna de agua dulce y el desarrollo de la hidroeléctrica. Las turbinas hidroeléctricas ponen a los peces en riesgo de heridas severas al pasar por ellas. Por lo tanto, análisis integrales, confiables de la mortalidad de peces inducida por turbinas son esenciales para sustentar un debate informado de la sustentabilidad de la energía hidroeléctrica (i. e., que tan dispuesta esta una sociedad para pagar en términos de costos incurridos en los ríos y su biota). Compilamos y examinamos un conjunto de datos integrales, globales de evaluaciones de mortalidad de peces en turbinas involucrando >275, 000 peces individuales de 75 especies para estimar la mortalidad en tipos de turbinas y especies de peces. La mortalidad promedio de peces en turbinas hidroeléctricas fue 22.3% (95% IC 17.5‐26.7%) cuando se consideraron incertidumbres comunes relacionadas con las estimaciones empíricas (e. g., efectos relacionados con el manejo o captura). Las estimaciones de mortalidad fueron muy variables entre y dentro de los diferentes tipos de turbinas, métodos de estudio y taxones. Las configuraciones técnicas de las turbinas hidroeléctricas que exitosamente reduzcan la mortalidad de peces y proporcionen una operación protectora de peces como un estándar global podrían equilibrar la necesidad de energía renovable con la protección de la biodiversidad de peces. 鱼类通过水电涡轮机时存在明显的但与环境相关的死亡现象: 【摘要】 在全球范围内, 旨在保护物种、促进河流自由流动, 以及促进水电作为可再生能源及作为能源系统碳减排方法的政策在保护淡水动物和开发水电之间存在着利弊权衡。鱼类在通过水电涡轮机时面临受到严重伤害的风险。因此, 对水电涡轮机引起的鱼类死亡情况进行全面、可靠的分析, 对于支持关于水电可持续性的基于知识的辩论(即社会愿意为河流及其生物群落付出多少成本)至关重要。我们整理并分析了一个全面的全球涡轮机导致鱼类死亡的评估数据集, 涉及75种鱼类超过275, 000条个体, o以估计不同类型的涡轮机引起的不同鱼类物种的死亡率。我们将经验估计中常见的不确定性(如处理或捕鱼相关的影响)纳入考虑, 发现水电涡轮机导致的鱼类平均死亡率为22.3%(95%CI为17.5‐26.7)。不同涡轮机类型、研究方法, 以及鱼类类群组内和组间的鱼类死亡率估计值都有很大差异。我们建议将成功降低鱼类死亡率并能为鱼类提供保护的水电装置作为全球水电涡轮机的标准技术配置, 以平衡对可再生能源的需求与对鱼类生物多样性的保护。【翻译: 胡怡思;审校:聂永刚】